Dynamics of coordination within elite rowing crews: evidence from force pattern analysis - Hill, H. (Journal of Sports Sciences, 2002)
For a rowing crew to be successful, the movements of the rowers need to be well coordinated. Because rowers show individual force patterns, they have to adapt their movements when rowing as a crew. In this exploratory study, these hypothesized changes in movement pattern were examined. The force graphs of six elite coxless fours crews were recorded over 11 training runs using strain gauges attached to the oars. A detailed force analysis showed that form differences, but not area differences, between force patterns decreased when force output increased as a result of two different processes. First, increasing force output reduced form differences instantaneously by reducing the individual variation in force patterns. Secondly, the kinaesthetic perception of form differences is easier than that of area differences. This better perception facilitates the adaptation of movement patterns, especially when force output is high.